1997
DOI: 10.1021/jp970781z
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Laser Spectroscopy of the Water Pentamer:  Structure and Hydrogen Bond Rearrangement Dynamics

Abstract: The detailed analysis of a parallel vibration−rotation-tunneling (VRT) band of the isolated cyclic perdeuterated (d 10) water pentamer measured near 2.4 THz (81.2 cm-1) is presented. The vibrationally averaged rotational constants correspond rigorously to those of a quasiplanar (C 5 h ) oblate top whereas the equilibrium cyclic structure is predicted to be slightly asymmetric due to puckering of the oxygen framework and uneven distribution of the free O−D bonds above and below the ring. The vibrational averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 81 publications
5
101
0
Order By: Relevance
“…Qualitative estimates for the magnitude of the splittings suggested that the flip should lead to observable effects in both (H 2 O) 5 and (D 2 O) 5 , while bifurcation tunneling might produce splittings at the limit of current resolution [31]. The latest experimental results appear to be in agreement with these predictions [77]. …”
Section: Water Pentamermentioning
confidence: 52%
“…Qualitative estimates for the magnitude of the splittings suggested that the flip should lead to observable effects in both (H 2 O) 5 and (D 2 O) 5 , while bifurcation tunneling might produce splittings at the limit of current resolution [31]. The latest experimental results appear to be in agreement with these predictions [77]. …”
Section: Water Pentamermentioning
confidence: 52%
“…42,43 The size of a given water cluster responsible for an observed absorption feature was determined from an isotope mixture test described previously, 34 wherein the absorption line intensity was measured as a function of the H mole fraction in the H 2 O + D 2 O mixture employed for the production of water clusters. Careful intensity normalization 44 was performed by measuring the signals alternately between an isotope mixture and a pure reference sample. The logarithm of normalized intensities plotted against the H mole fraction ( Figure 2) established a cluster size of 5.99 ( 0.15 to 95% confidence, hence clearly establishing the hexamer as the spectral carrier.…”
Section: Methodsmentioning
confidence: 99%
“…The model of WW provided a reasonable first approximation to the torsional-puckering energy manifold; however, Liu et al 13 argued that the perturbative tunneling model of WW was insufficiently developed to fully characterize the hindered rotational motions of the water pentamer. Liu et al indicated two major shortcomings of the tunneling model of WW: (1) It only predicted a number of energy levels equal to the order of the MS group, nominally ten, since splittings beyond the ground state were not included.…”
Section: Theoretical Considerationsmentioning
confidence: 99%